Answer :

LHS = A ∩ (A B)’

Using De-Morgan’s law (A B)’ = (A’ ∩ B’)

⇒ LHS = A ∩ (A’ ∩ B’)

⇒ LHS = (A ∩ A’) ∩ (A ∩ B’)

We know that A ∩ A’ = ϕ

⇒ LHS = ϕ ∩ (A ∩ B’)

We know that intersection of null set with any set is null set only

Let (A ∩ B’) be any set X hence

⇒ LHS = ϕ ∩ X

⇒ LHS = ϕ

⇒ LHS = RHS

Hence proved

Rate this question :

Prove that A ∩ (A B)’ = ϕ

RS Aggarwal - Mathematicsif U = {a, b, c} and A = {a, c, d, e} then verify that:

(i) (A ∪ B)’ = (A’ ∩ B’)

(ii) (A ∩ B)’ = (A’ ∪ B’)

RS Aggarwal - Mathematics

For any two sets A and B, prove the following:

A ∩ (A’ ∪ B) = A ∩ B

RD Sharma - MathematicsFor any two sets A and B, prove the following:

A – (A – B) = A ∩ B

RD Sharma - MathematicsFor any two sets A and B, prove that

(A – B) ∪ (A ∩ B) = A

RD Sharma - MathematicsIf A, B, C are three sets such that A ⊂ B, then prove that C – B ⊂ C – A.

RD Sharma - MathematicsFor any two sets A and B, prove that

(A ∪ B) – B = A – B

RD Sharma - MathematicsFor any two sets A and B, prove the following:

A – B = A Δ (A ∩ B)

RD Sharma - Mathematics